Fighting in the Shadow of an Apartheid State: Boxing and Colonialism in Zimbabwe - Seda, Abraham (Kronos: Southern African Histories, 2024)
Boxing was arguably the most popular and controversial sport in colonial Zimbabwe. To tame the sport's violence, which was considered too extreme, colonial officials in Zimbabwe sought guidance and advice from South Africa from the mid-1930s on how best to regulate the sport. South Africa occupied a unique position in this regard, not only because of the relationship it had with colonial Zimbabwe as a neighbouring white settler colony, but also because of how sections of its white settler community responded to the triumphs of Black boxers over white opponents around the world. The colony of South Africa played a significant role in shaping the control of boxing in colonial Zimbabwe. The relationship between the two colonies culminated in the passage of the Boxing and Wrestling Control Act of 1956 in colonial Zimbabwe, an identical version to a similarly named law that South Africa had passed just two years prior.